The Identification of Critical m6A RNA Methylation Regulators as Malignant Prognosis Factors in Prostate Adenocarcinoma - Xu, Jiaju; Liu, Yuenan; Liu, Jingchong; Xu, Tianbo; Cheng, Gong; Shou, Yi; Tong, Junwei; Liu, Lilong; Zhou, Lijie; Xiao, Wen; Xiong, Zhiyong; Yuan, Changfei; et al. (Frontiers in Genetics, 2020)
RNA methylation accounts for more than 60% of all RNA modification, and N6-methyladenosine (m6A) is the most common modification on mRNA and lncRNA of human beings. It has been found that m6A modification occurs in microRNA, circRNA, rRNA, tRNA, etc. The m6A modification plays an important role in the regulation of gene expression, and the abnormality of its regulatory mechanism refers to many human diseases, including cancers. Pitifully, it stands lack of knowledge of the extent that the expression and function of m6A RNA methylation influence prostate cancer. Herein, we systematically analyzed the expression levels of 35 m6A RNA methylation regulators mentioned in literatures among prostate adenocarcinoma patients in the Cancer Genome Atlas (TCGA), finding that most of them expressed differently between cancer tissues and normal tissues with the significance of p<0.05. Utilizing consensus clustering, we divided prostate cancer patients into two subgroups based on the differentially expressed m6A RNA methylation regulators with significantly different clinical outcomes. To appraise the discrepancy in total transcriptome between subgroups, the functional enrichment analysis was conducted for differential signaling pathways and cellular processes. Next, we selected five critical genes by the criteria that the regulators had a significant impact on prognosis of prostate cancer patients from TCGA through the last absolute shrinkage and selection operator (LASSO) Cox regression and obtained a risk score by weighted summation for prognosis prediction. The survival analysis curve and receiver operating characteristic (ROC) curve showed that this signature could excellently predict the prognosis of prostate cancer patients. The univariate and multivariate Cox regression analyses proved the independent prognostic value of the signature. In summary, our effort revealed the significance of m6A RNA methylation regulators in prostate cancer and determined a m6A gene expression classifier that well predicted the prognosis of prostate cancer.